IMPLEMENTASI STRATEGI MANAJEMEN PEMBIAYAAN PENDIDIKAN PADA SEKOLAH DASAR NEGERI 42 TALANG UBI - Saipul Anwar; Asbiri; Nurlaili; Kasinyo Harto; Fitri Oviyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the implementation of educational financing management strategies at Public Elementary School 42 Talang Ubi. The research aims to analyze how the school conducts financial planning, allocation, utilization, and evaluation to support the achievement of its educational objectives. Employing a qualitative descriptive approach, data were collected through interviews, observations, and document analysis. The results indicate that the school adopts several strategic measures, including participatory budgeting involving key stakeholders, expenditure prioritization based on academic and operational needs, and the practice of transparent financial reporting. These strategies have contributed to more efficient and accountable financial management, thereby supporting the quality of educational services. Nevertheless, the school continues to face challenges such as limited funding sources, dependence on government allocations, and delays in fund disbursement. The findings underscore the critical role of strategic financial management in enhancing educational effectiveness at the elementary level. The study recommends strengthening institutional capacity in financial management and exploring alternative funding mechanisms to ensure the sustainability of educational programs.